Darkness and gulliver2/phyB mutation decrease the abundance of phosphorylated BZR1 to activate brassinosteroid signaling in Arabidopsis. (4th February 2014) - Kim, Bokyung; Jeong, Yu Jeong; Corvalán, Claudia; Fujioka, Shozo; Cho, Seoae; Park, Taesung; Choe, Sunghwa
Summary Light is essential for plant survival; as such, plants flexibly adjust their growth and development to best harvest light energy. Brassinosteroids (BRs), plant growth‐promoting steroid hormones, are essential for this plasticity of development. However, the precise mechanisms underlying BR‐mediated growth under different light conditions remain largely unknown. Here, we show that darkness increases the activity of the BR‐specific transcription factor, BZR1, by decreasing the phosphorylated (inactive) form of BZR1 in a proteasome‐dependent manner. We observed that COP1, a dark‐activated ubiquitin ligase, captures and degrades the inactive form of BZR1. In support of this, BZR1 is abundant in the cop1‐4 mutant. The removal of phosphorylated BZR1 in darkness increases the ratio of dephosphorylated to phosphorylated forms of BZR1, thus increasing the chance of active homodimers forming between dephosphorylated BZR1 proteins. Furthermore, a transcriptome analysis revealed the identity of genes that are likely to contribute to the differential growth of hypocotyls in light conditions. Transgenic misexpression of three genes under the 35S promoter in light conditions resulted in elongated petioles and hypocotyls. Our results suggest that light conditions directly control BR signaling by modulating BZR1 stability, and consequently by establishing light‐dependent patterns of hypocotyl growth in Arabidopsis.